Penanganan Tindak Pidana Narkotika Di Kota Ambon Oleh Direktorat Reserse Narkoba Polda Maluku - Pricilya Melany Anthonio; Juanrico Alfaromona Sumarezs Titahelu; Judy Marria Saimima (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: Narcotics abuse in Ambon City has increased from 2018-2021. Narcotics in 2018-2021, namely: in 2018 there were 140 cases, in 2019 there were 123 cases, in 2020 there were 143 cases while in 2021 there were 169 cases.Purposes of the Research:  To examine and discuss what was carried out by drug investigators from the Maluku Regional Police in handling narcotics crimes. To examine and discuss the obstacles faced by drug investigators from the Maluku Regional Police in handling narcotics crimesMethods of the Research: This research is a normative juridical research. This type of research is descriptive analytical. The source of legal materials used in this research is primary legal materials and secondary legal materials. Supporting data and information are then identified and then systematized for interpretation and given arguments to draw conclusions on the problem.Results of the Research: What the Maluku Police drug investigators did in handling narcotics crimes, namely: conducting examinations of witnesses and suspects and completing investigative actions, confiscating evidence found on suspects, conducting examinations or testing of evidence found on suspects, sending SPOP (Notification Letter of Commencement Investigation) to the Prosecutor's Office, carrying out the filing process, Submission of suspects and evidence to the prosecutor besides that there are obstacles faced by Maluku Police Narcotics investigators in Handling narcotics crimes, namely: there is still a lack of good cooperation between the community and officers, the modus operandi carried out by actors who are growing and changing, there are many new variants of narcotics.